Pengaruh Terapi Pijat terhadap Kenaikan Berat Badan Balita di PMB Bidan Lena Rangkapan Jaya Kota Depok Tahun 2023 - Nur Faizah; Lisa Trina Arlym; Rukmaini Rukmaini (Poltekkes Kemenkes Padang, 2023)
The 1000 HPK period is important in the process of growth and development of children in obtaining optimal nutritional intake. One of the non-pharmacological ways that is done is by giving massage therapy. The research objective was to determine the effect of massage therapy on toddlers' weight gain and the differences in weight gain between the intervention and control groups. This research is a quasi-experimental design, a pretest-posttest control group design and a combination intervention of healthy massage therapy and the elderly. Therapy was given 6x/week consecutively for 1 month, weighing was carried out on the 7th, 14th, 21st and 28th days. The purposive sampling sample consisted of 30 toddlers. Data analysis paired t-test and independent t-test. Results of data analysis paired t-test p-value 0.000<0.05. The mean difference in the intervention group on day 7: 160 grams, 14th: 353.333 grams, 21st: 626.667 grams, 28th: 986.667 grams. The mean difference in the control group on day 7:86.667 grams, 14th: 193.333 grams, 21st: 300 grams, 28th: 440 grams. Independent t-test results with a p-value of 0.034<0.05 on the 21st day and a p-value of 0.011<0.05 on the 28th day. There is an effect of massage therapy on toddlers' weight gain. There are differences in toddlers' weight gain between the intervention group and the control group. It is hoped that all health workers and families can apply it to toddlers to prevent malnutrition.